ABUSE PRACTICE OF POWER IN ORWELL'S ANIMAL FARM: A HISTORICAL APPROACH - Hasan, Mariwan; Muhammad, Lava; Bahasin, Gashbin (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2020)
It occurs very often to observe the exploitation of common people by the politicians owing to leader’s bad use of absolute power and the silence of the people. It appears that knowledge and education will lead to absolute power which culminates in suffering and oppression of simple and naïve people in the Soviet Union.The language used in Animal Farm was not known by the majority and this leads to threat through different principles and laws. This enabled the leaders to exploit the others for their greedy desires and to do abnormal actions.  As a result of the use of a vague language and the implementation of fear tactics then creating laws to help them to manipulate others, they could convince them and then they invented lies at the interest of leaders. Yet the others due to their simplicities were easily convinced, while power could be used to serve the entire population of the Soviet Union. The study uses historical approach for the analysis of the research.